THE COSSACS IN THE MORET-SUR-LOING, OR WHY THE MAYOR'S WIFE CAN'T BE OFFENDED - Andrey Gladishev (Гуманитарные и юридические исследования)
The paper deals with an episode of the 1814 campaign in France - the sojourn of Allied troops in Moret-sur-Loing. In this city there were Cossacks besides the Austrians in February 1814. The image of the Cossack formed in the early twentieth century by a local historian G. Lioret is borrowed uncritically by the later historiography, which requires comments and clarifications.